PAŃSTWO KONTRAKTUJĄCE: REFORMA SEKTORA PAŃSTWOWEGO W NOWEJ ZELANDII - Swora, Mariusz (Wydział Prawa i Administracji UAM, 2005)
The paper deals with the organisational and legal aspects of the reform of the public sector in New Zealand. The reform, conducted in the spirit of recommendations of the New Public Management, had substantially transformed the whole government administration, and has become internationally recognised as an example of far reaching and consistent transformations in the public administration, leading to the introduction in it of certain managerial elements. Two aspects of New Zealand’s reforms are discussed in detail: the system of contracting tasks and the transformation of the public service. Possibilities of applying the same solutions in other states are also looked upon.
A CONTRACTING STATE: REFORM OF THE STATE SECTOR IN NEW ZEALAND